Tennis : for boys and girls : start right and play well - Gutman, Bill.; Brown, Ben, 1921- (Freeport, N.Y. : M. Cavendish Corp. ; Lakeville, Ct. : Grey Castle Press, 1990)
Describes the history and current teams, leagues, and championships of tennis and provides instruction on how to play the game.
Keywords: Tennis -- Juvenile literature; Tennis